THE RELATIONSHIP BETWEEN SMARTPHONE USE INTENSITY AND THE DEVELOPMENT OF CHILDREN AGED 4-6 YEARS IN KINDERGARTEN - Erika Febriyanti; Indah Mawarti; Lisa Anita Sari; Fadliyana Ekawaty; Kamariyah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Background: The use of smartphones among preschool children has increased along with the development of digital technology. Children aged 4–6 years are in a golden period of development, which includes gross motor skills, fine motor skills, speech and language, socialization, and independence. This study aimed to determine the relationship between the intensity of smartphone use and the development of children aged 4–6 years at TK Negeri Pembina 2 Kota Jambi. Methods: This study employed a cross-sectional design. The sampling technique used was total sampling, with 88 children who met the inclusion criteria as respondents. Data on the intensity of smartphone use were obtained through a questionnaire completed by parents, while child development was assessed using the Developmental Pre-Screening Questionnaire (KPSP). Results: Most children had a moderate level of smartphone use intensity (40.9%), and child development was predominantly in the appropriate category (53.4%). The Spearman Rank correlation test showed a correlation coefficient of r = −0.794 with a significance value of p < 0.001, indicating that H1 was accepted and H0 was rejected. These results demonstrate a strong relationship between the intensity of smartphone use and child development. Conclusion: Higher intensity of smartphone use may lead to a decrease in child development. Therefore, it is expected that schools can collaborate with parents to provide education regarding the wise use of smartphones for preschool children.